Indonesian Teachers’ Self-Regulation, Their Self-Concept of Competence and Satisfaction in Teaching - Rachelina Larasati; Paulus Kuswandono (UNIB Press, 2022)
It has been acknowledged in the literature that a good self-concept of teachers will enable teachers to adapt to changing situations, which might result in effective teaching that will benefit students. On the contrary, negative self-concept results in teachers’ burnout and inability to perform well in teaching. This mixed-methods study aims to investigate whether teacher self-concept can be enhanced by the implementation of self-regulation strategies. Two research questions are formulated in this study: (1) To what extent do Indonesian teachers implement self-regulation in their teaching? (2) What is the correlation between teachers’ self-regulation and the concept of their competency and satisfaction in teaching? In the quantitative phase, sixty teachers from different parts of Indonesia participated in the study by completing an online questionnaire. The data gathered was submitted to the SPSS and was analyzed using the Pearson correlation method. The result showed that there were positive correlations between teacher self-regulation and teacher self-concept of competence with r=.381 and satisfaction with r=.372. To gain a deeper understanding, in the qualitative phase, interviews were done with three of the teachers. The data resulted that teachers have highly implemented teacher self-regulation and affirmed that it has contributed to the enhancement of their self-concept of competence and satisfaction.